-2(5x+5)-3x+4=-3

Simple and best practice solution for -2(5x+5)-3x+4=-3 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -2(5x+5)-3x+4=-3 equation:



-2(5x+5)-3x+4=-3
We move all terms to the left:
-2(5x+5)-3x+4-(-3)=0
We add all the numbers together, and all the variables
-3x-2(5x+5)+7=0
We multiply parentheses
-3x-10x-10+7=0
We add all the numbers together, and all the variables
-13x-3=0
We move all terms containing x to the left, all other terms to the right
-13x=3
x=3/-13
x=-3/13

See similar equations:

| -9(y-7)=6y+45 | | 3(x+6)=4848 | | 3/4x+-2=2 | | 5u+2=-3(u-6) | | -15-6m=2(-3m-5) | | 3x+7x+5=x-2-11 | | 5a+1=-29 | | {3}{4}x+-2=2 | | 7v+6=-71 | | 2-14f+17=19-14f | | 1c-6=c | | 5.9g+2=2.9g+8 | | 10x-10=4x-20 | | 3x-7+2x=5x | | -3x^2+3x-6=0 | | –21=3(c+1) | | 7.6=3(y-4.9)-2 | | 5/b=7/4 | | 10n=-8(-n+13) | | 15-6p=-29 | | –4=–w–12 | | 4.5g+8=2.5g+12 | | 2(d+11)=-4 | | 5z-9=31 | | 2x(-4)/4=3 | | 7x-12+6x+4=5x | | 2(k+3)+1.7=9.7 | | 10n=(-n+13) | | -8x+-2=-26 | | 3a−5=-14 | | 1b-10=-13 | | 6.8g+8=2.8g+32 |

Equations solver categories